Les crocodiles marins du Jurassique normand - Alma Hueber (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
As part of my Master's thesis, we worked on fossils and plaster casts entrusted by the National Museum of Natural History. The study and restoration of these fossils and plaster casts were a great opportunity to face specific demands and different types of objects. The composition of the specimens was widely investigated, and the presence of pyrite in a fossil influenced our intervention methods. The molding on the half-crane was an opportunity to approach molding in a scientific and educational context by realizing a rebuilding of the rostrum.